Method for preparing high-performance hollow glass bead / epoxy resin floating body material
By surface modification and bonding of hollow glass microbeads with polyether ether ketone, porous preforms were prepared and epoxy resin was injected under vacuum for curing, the problem of poor uniformity and bubble mixing in the hollow glass microbead floating material molding process was solved, and the mechanical properties of the material were improved.
Patent Information
- Application Number
- CN202411879637.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
There are problems of poor uniformity, crushing of microbeads and bubbles in the molding process of existing hollow glass microbeads, which affect the mechanical properties of the material.
By hydroxylation and coupling agent coating on hollow glass microbeads, combined with the bonding effect of polyether ether ketone, a porous preform was prepared, and epoxy resin was injected under vacuum to cure to avoid the formation of bubbles.
The filling rate and uniformity of hollow glass microbeads in the epoxy resin matrix are improved, pore defects are reduced, and the mechanical properties of the floating material are significantly enhanced.
Smart Images

Figure CN119684747A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of solid floating material preparation, and in particular relates to a method for preparing a high-performance hollow glass microsphere / epoxy resin floating material. Background Art
[0002] Solid floating materials (also known as solid buoyancy materials) play a key role in deep-sea equipment and are extremely critical core materials in marine exploration and deep-sea engineering. Solid floating materials can generally be divided into three categories: chemical foaming floating materials and composite lightweight floating materials (two-phase composite foam materials, three-phase composite foam materials). Two-phase composite foam materials only contain lightweight fillers and resin matrices, while three-phase composite foam materials contain irregular bubble phases.
[0003] Hollow microsphere floating material is mainly made of hollow glass microspheres and resin substrates by thermal curing. It is the most reported type of solid floating material at home and abroad. The microspheres filled in hollow microsphere materials are mainly divided into two categories: inorganic and organic. Inorganic microspheres mainly include SiO 2 、Al 2 O 3 , ceramics, etc. Organic microspheres include epoxy, phenolic and polystyrene balls. Common resins include epoxy resin, phenolic resin, unsaturated polyester, etc. The molding methods are generally stirring casting, vacuum impregnation, etc. This material has the characteristics of low density, high strength, resistance to hydrostatic external pressure, resistance to seawater corrosion, low water absorption, etc. It can withstand huge pressure thousands of meters underwater, and its own density is lower than the density of water, which can provide buoyancy to support underwater robots and their own weight.
[0004] However, the current molding process for hollow microsphere floating materials is mostly the stirring casting method, which has the following problems: the density of HGM (hollow glass microspheres) is lower than the density of polymers, which will cause the microspheres to float during the stirring process, resulting in poor uniformity of the composite material; too high a stirring speed will cause the microspheres to break, thereby increasing the density of the composite material; when preparing a high volume fraction HGM composite hollow microsphere floating material, due to the low polymer content, the viscosity of the mixed slurry of microspheres and polymers will be too high, which is not conducive to stirring, and during the stirring process, bubbles that are difficult to remove will be mixed into the material, seriously affecting the performance of the composite material.
[0005] Song Yuting et al. mixed two different types of modified hollow glass microspheres in proportion, and then stirred, poured and cured them with an epoxy resin system to obtain a mixed hollow glass microsphere composite floating material. The use of hollow glass microspheres of different particle sizes can improve the filling rate of hollow glass microspheres in the composite material and effectively reduce the density of the composite material. However, the poor uniformity of the composite material caused by the stirring and pouring method and the problem of bubbles mixed into the material have not been solved (Chinese patent application number: CN112694717B). Liang Xiaojie et al. prepared the composite material by vacuum impregnation, and removed bubbles several times during the process of adding raw materials, effectively removing most of the bubbles in the composite material. However, during the vacuum impregnation process, there are some requirements for the shape of the mold. Because the gaps between the hollow glass microspheres are small, the epoxy resin may not be fully infiltrated and will flow out from the glue outlet (Chinese patent application number: CN110698815B). Tang Bo et al. grafted polyetheretherketone on the surface of hollow glass microspheres, and then mixed it with epoxy resin by stirring and pouring to make a floating material. After testing, this method has the phenomenon of uneven distribution of hollow glass microspheres in the epoxy resin matrix (Chinese patent application number: CN103865235A). Shi Qiankun et al. used polyethylene, polypropylene, and polyamide instead of conventional epoxy resin as the matrix material, and sent the matrix mixture and the modified hollow glass microspheres into a twin-screw extruder. After the extruder melted and extruded the material, it was molded and cooled to obtain a solid floating material. They used a screw extruder to achieve large-scale preparation, with a high degree of automation and low labor costs. However, since the material molding process is implemented by machinery, it is impossible to specifically solve the problem of poor material uniformity, and a large number of bubbles will be mixed in the molding process and cannot be removed, which will affect the mechanical properties of the material (Chinese patent application number: CN202410336855.5). An Zhenguo and his colleagues used hollow composite microbeads with a double-layer spherical shell structure with an outer shell of metal oxide and an inner shell of silicate glass, mixed the resin and curing agent with the hollow composite microbeads respectively, and then mixed and vibrated the two mixtures to remove bubbles, thereby obtaining a lightweight and high-strength solid floating material. Although this method has a degassing process, it does not solve the problem of poor material uniformity caused by the floating of microbeads during the mixing process of the microbeads and the matrix (Chinese patent application number: 202011108682.X). Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention proposes a method for preparing a high-performance hollow glass microsphere / epoxy resin floating material. The method can improve the filling rate of hollow glass microspheres in the epoxy resin matrix, and at the same time remove the gas mixed in the hollow glass microsphere filling process, avoid the residual pore defects of the material after curing, and effectively enhance the mechanical properties of the floating material.
[0007] To achieve the above objectives, the technical solution of the present invention is implemented through the following technical solutions:
[0008] A method for preparing high-performance hollow glass microsphere / epoxy resin floating material, the preparation process of which is as follows:
[0009] (1) hydroxylating and coupling agent coating the hollow glass microspheres to obtain surface-treated hollow glass microspheres;
[0010] (2) mixing the surface-treated hollow glass microspheres and polyetheretherketone in a uniform proportion, placing them into a mold and sintering them in a muffle furnace, wherein the sintering process is as follows: heating to 370°C-380°C at a heating rate of 5-10°C / min and keeping the temperature for 15-20min, cooling, and demolding to obtain a porous preform; wherein the mass ratio of the surface-treated hollow glass microspheres to the polyetheretherketone is 30:4-8;
[0011] (3) mixing the epoxy resin and the curing agent in proportion and stirring evenly to obtain an epoxy resin mixed solution;
[0012] (4) placing the porous preform obtained in step (2) in a cavity mold, injecting the epoxy resin mixture obtained in step (3), evacuating and maintaining pressure for a period of time, heating and curing, cooling, and demolding.
[0013] Since hollow glass microspheres are hollow structures with good thermal insulation effects, a too low heating rate will affect the molding speed; a too fast heating rate will cause the polyetheretherketone in the edge area to melt too quickly, while the center glass will still be in a powdery solid state, which will have an adverse effect on the molding of the porous preform.
[0014] A high temperature resistant coupling agent is used to avoid the volatilization of the coupling agent in the high temperature environment of 370℃-380℃ for the preparation of the preform, which leads to a decrease in the interfacial bonding strength between the hollow glass microspheres and the epoxy resin and polyetheretherketone, and ultimately affects the performance of the composite material. The high temperature resistant KH-792 is used because KH-792 is resistant to high temperatures and because the epoxy group (γ-glycidyl) of KH-792 can react chemically with the hydroxyl or amine group in the epoxy resin to form a strong covalent bond, thereby ensuring high bonding strength with the epoxy matrix. At the same time, its trimethoxysilyl group forms a stable silicon oxygen bond (Si-O-Si) with the hydroxyl group on the glass surface after hydrolysis, significantly enhancing the interfacial bonding performance between the glass and the organic matrix. This dual function gives KH-792 a significant advantage in improving the interfacial bonding strength and durability of composite materials. In addition, the bonding stability of KH-792 under wet heat and long-term service conditions is better. Therefore, by modifying the surface of the hollow glass microspheres, the interfacial bonding force between the hollow glass microspheres and the polyetheretherketone can be improved, and the bonding between the hollow glass microspheres and the polyetheretherketone can be made tighter.
[0015] In a preferred embodiment, step (2) is specifically as follows: mixing the surface-treated hollow glass microspheres with polyetheretherketone powder and pouring them into a mold, placing the mold containing the surface-treated hollow glass microspheres and polyetheretherketone powder on an oscillating device, and oscillating for a period of time so that the polyetheretherketone powder is evenly mixed on the surface of the hollow glass microspheres and fully densely stacked; then, placing the mold containing the densely stacked polyetheretherketone powder and hollow glass microspheres into a muffle furnace, gradually heating to 370°C-380°C, keeping warm for 15-20 minutes, cooling to room temperature, demolding, and obtaining a hollow glass microsphere / polyetheretherketone porous preform. If the temperature is lower than 370°C, the preform cannot be formed; if the temperature is too high (for example, above 400°C), polyetheretherketone PEEK will undergo thermal degradation, which is manifested as the breakage of the molecular chain, the generation of harmful gases or degradation products, and the color of the material will also become darker or yellower.
[0016] The mold for containing the surface-treated hollow glass microspheres and polyetheretherketone in step (2) is a quartz mold.
[0017] Before the hollow glass microspheres are subjected to hydroxylation and coupling agent coating treatment in step (1), the hollow glass microspheres are subjected to flotation treatment; in the flotation treatment, the operation steps are: mixing the hollow glass microspheres with pure water in proportion, stirring at a certain speed, taking the upper layer of microspheres after standing for a certain time, and drying to obtain the hollow glass microspheres after flotation; in the flotation treatment, when the hollow glass microspheres are soaked in pure water, the volume ratio of the hollow glass microspheres to water is 1:8-12; in the flotation treatment, the stirring time is 5-15 minutes, and the mixture needs to be stood for 1-3 hours after stirring.
[0018] In step (1), the hollow glass microspheres are hydroxylated with a 0.6-1.0 mol / L NaOH solution, and the solution is stirred during the hydroxylation. During the hydroxylation, the temperature is 40-60° C., the treatment time is 1.5-2.5 h, and the stirring rate is 300-500 rpm. The mass volume ratio of the hollow glass microspheres to the NaOH solution is 1 g: (8-12) mL.
[0019] During the coupling agent coating process, the hollow glass microbeads after hydroxylation treatment are placed in an ethanol solution, which is a mixture of anhydrous ethanol and deionized water in a volume ratio of 1:3, and then a high-temperature resistant silane coupling agent is added, and the mixture is stirred at 70-90°C for 1.5-2.5h; the hollow glass microbeads after surface treatment are taken, washed, and dried at 110-120°C to complete the curing of the coupling agent and the formation of chemical bonds.
[0020] During the coupling agent coating process, the coupling agent used is the high temperature resistant silane coupling agent KH-792, the mass ratio of the coupling agent to the hollow glass microspheres after hydroxylation is 1:7-13; the mass volume ratio of the hollow glass microspheres after hydroxylation to the ethanol solution is 1g:(20-40)mL.
[0021] In step (3), the mass ratio of epoxy resin to curing agent is 2.5-3.5:1; the epoxy resin is liquid epoxy resin.
[0022] In step (3), the epoxy resin is E-51 epoxy resin, and the curing agent is amine curing agent HS-273M.
[0023] Step (4) is specifically as follows: placing the porous preform obtained in step (2) in a mold, pouring the epoxy resin mixture obtained in step (3) into the mold, and making the epoxy resin mixture just submerge the porous preform (the open porosity of the porous preform is a, a is subject to actual measurement, the volume of the porous preform is V, and when the porous preform is prepared in step (2), the porous preform fills the cavity in the mold, and the volume of the cavity in the mold is V. When the epoxy resin mixture just submerges the porous preform, the volume of the epoxy resin mixture is V*(a+1%)~V*(a+3%); placing the entire mold in a vacuum box, evacuating and maintaining pressure until the epoxy resin does not boil, and a hollow glass microsphere preform filled with liquid epoxy resin is formed in the mold; taking out the hollow glass microsphere preform filled with liquid epoxy resin together with the mold, heating to 70-90°C and keeping warm for 4-6 hours, cooling after solidification, and demolding to obtain the final floating material.
[0024] Preferably, in step (1), before the hollow glass microspheres are subjected to hydroxylation and coupling agent coating treatment, the hollow glass microspheres are subjected to flotation treatment: when the hollow glass microspheres are soaked in pure water, the volume ratio of the hollow glass microspheres to water is 1:10. The stirring time is 10 minutes, and the mixture needs to be allowed to stand for another 2 hours after stirring. The specific operation of the flotation treatment is: the hollow glass microspheres are mixed and stirred with pure water in proportion, the upper layer of microspheres is taken after standing, and the hollow glass microspheres are filtered and dried to obtain the hollow glass microspheres after flotation.
[0025] In this article, taking the upper layer of microbeads refers to taking the microbeads floating on the water surface, which is to remove the microbeads with damaged surfaces that cannot float normally.
[0026] Preferably, when the hollow glass microspheres are subjected to hydroxylation treatment in step (1), the concentration of the NaOH solution is 0.75 mol / L. The dosage of the hollow glass microspheres is 10 g per 100 ml of NaOH solution. The water bath stirring temperature is 50°C, the stirring time is 2 h, and the stirring rate is 400 rpm. The specific operation is: add an appropriate amount of hollow glass microspheres to 100 mL of NaOH solution and stir in a water bath for a period of time. Take the upper layer of hollow glass microspheres after stirring, wash with deionized water until neutral, and obtain hydroxylated hollow glass microspheres after suction filtration and drying.
[0027] Preferably, in the step (1), the hollow glass microspheres after hydroxylation are coated with a coupling agent, and the ethanol solution is formed by mixing anhydrous ethanol and deionized water in a volume ratio of 1:3. The ethanol solution required for every 10g of hollow glass microspheres is 300mL. The amount of coupling agent used is 1g. The specific operation is: place the hollow glass microspheres after hydroxylation in an ethanol solution, add 1g of coupling agent, and stir in a water bath for a period of time. Take the upper layer of hollow glass microspheres after stirring, wash the microspheres with deionized water, filter and dry them, and finally obtain hollow glass microspheres after surface treatment.
[0028] Preferably, in step (2), the ratio (mass ratio) of the surface-treated hollow glass microspheres and the polyetheretherketone powder is 30:4, 30:5, 30:6, 30:7, or 30:8.
[0029] Preferably, in the step (2), the sintering temperature of the surface-treated hollow glass microspheres and polyetheretherketone is 370°C.
[0030] Preferably, in step (2), the mold containing the surface-treated hollow glass microspheres and polyetheretherketone is a quartz mold.
[0031] Preferably, in the step (2), the specific operation is to mix the surface-treated hollow glass microspheres with the polyetheretherketone powder and pour them into a quartz mold, place the mold on an oscillation device, and oscillate for a period of time (10-20 minutes) to make the powders evenly mixed and fully densely stacked. Then, the mold containing densely stacked powder and hollow glass microspheres is placed in a muffle furnace, and the temperature is raised to 370°C according to a preset sintering program. After keeping the temperature at 370°C for a certain period of time, the mold is taken out and demolded after cooling to room temperature to obtain a hollow glass microsphere / polyetheretherketone porous preform.
[0032] Preferably, in step (3), the ratio (mass ratio) of epoxy resin to curing agent is 3:1.
[0033] Preferably, in step (3), the porous preform obtained in step (2) is placed in a silicone rubber mold, and the epoxy resin mixture obtained in step (3) is poured into the silicone rubber mold to submerge the porous preform. The entire silicone rubber mold is placed in a small vacuum box, and after vacuuming and maintaining pressure for 20 minutes, it is observed that the epoxy resin has no boiling phenomenon. The hollow glass microsphere preform filled with liquid epoxy resin is taken out together with the mold, heated and cured, naturally cooled, and demolded to obtain the final floating material.
[0034] The processing temperature of polyetheretherketone powder is above 370°C and it will solidify when the temperature is lowered. The operation steps of the present invention are to evenly mix the two powders of polyetheretherketone and hollow glass microspheres, raise the temperature to 370°C-380°C to soften the polyetheretherketone, and then cool the polyetheretherketone to solidify and bond the hollow glass microspheres into a block. Too little polyetheretherketone cannot completely bond the hollow glass microspheres together to form flocs, and cannot play the role of fixing the hollow glass microspheres.
[0035] In material design, different materials are very sensitive to temperature. For example, in the present invention, the porous preform is prepared by bonding hollow glass microspheres with polyetheretherketone. The temperature must reach 370°C. Even 360°C or even 365°C will not be successfully prepared.
[0036] In the present invention, the hollow glass microspheres after surface treatment are mixed with polyetheretherketone to prepare a preform, and the phenolic hydroxyl group on the end group of polyetheretherketone can be used to cure with epoxy resin. The hybridization of epoxy resin and thermoplastic phase reduces brittleness and improves toughness without damaging thermal properties and mechanical properties. In addition, after the surface of the hollow glass microspheres is grafted with hydroxyl groups and silane coupling agents, the hydroxyl groups and silane coupling agents enhance the bonding performance of the hollow glass microspheres and polyetheretherketone. After the preform is formed, polyetheretherketone can also improve the interfacial bonding force between the hollow glass microspheres and epoxy resin. The curing of polyetheretherketone and epoxy resin improves the performance of the composite material. After the surface of the hollow glass microspheres is grafted with silane coupling agents, the surface will be cured with epoxy resin through epoxy groups to improve the performance of the composite material. That is to say, the method of the present invention can achieve the composite effects of toughening, strengthening, improving the filling rate of microspheres, dispersibility, etc. This cannot be achieved by using only epoxy resin and curing agent.
[0037] The present invention retains the integrity of the hollow structure of the hollow glass microspheres: if the preform is prepared by using the characteristics of the hollow glass microspheres softening and bonding together at high temperature (about 700°C), the hollow glass microspheres will be deformed and lose their hollow spherical characteristics, which will affect the strength and density of the composite material. In addition, at high temperature (about 700°C), the coupling agent grafted on the surface of the hollow glass microspheres will be separated from the surface of the hollow glass microspheres, resulting in a decrease in the subsequent interface bonding force between the hollow glass microspheres and the epoxy resin, affecting the strength of the composite material.
[0038] In the present invention, a relatively small amount of polyetheretherketone is used, which will not cause the problem of uneven distribution of microbeads. On the contrary, because the amount used is very small compared to the microbeads and epoxy resin, the hollow glass microbeads will be fixed in the best stacking manner when preparing the preform; if the amount of polyetheretherketone is too much, it will replace the position of the hollow glass microbeads, have a greater impact on the filling amount of the hollow glass microbeads, and ultimately affect the performance of the composite material.
[0039] The beneficial effects of the present invention are:
[0040] The present invention places a porous preform made by low-temperature pre-sintering of microspheres in a specific mold, then vacuumizes the mold, and then pours resin into it to fill the gaps between hollow glass microspheres, and finally solidifies and shapes it to obtain a solid floating material. The solid floating material obtained by the method has good uniformity, a high microsphere filling ratio, and because the bubble defects are removed during the molding process, the mechanical properties of the material are significantly improved.
[0041] The present invention has the following four advantages: (1) the high-temperature sintering method is replaced by a resin bonding method (hollow glass microspheres are bonded to prepare porous ceramic preforms using thermoplastic resin PEEK). High-temperature sintering causes the hollow glass microspheres to deform from hollow spherical shells to polygonal shells, affecting the performance of the final floating material, while the porous ceramic preform has no effect on the shape of the hollow glass microspheres; (2) the floating of the hollow glass microspheres due to density reasons is greatly reduced, making the hollow glass microspheres fill the resin matrix more uniformly; (3) there is no mixing and stirring of the hollow glass microspheres and epoxy resin, which reduces the breakage rate of the hollow glass microspheres; (4) the gas mixed in during the filling process of the hollow glass microspheres is removed, the pore defects remaining in the material after curing are avoided, and the mechanical properties of the floating material are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The flow chart of the preparation of the floating material of the present invention;
[0043] Figure 2 Macroscopic and microscopic morphology of HGM porous preform, a, macroscopic morphology, b, microscopic morphology;
[0044] Figure 3 Preforms that were successfully or unsuccessfully prepared: (a) Example 1, (b) Comparative Example 6;
[0045] Figure 4 Compression diagram of the float material of the present invention;
[0046] Figure 5 Stress-strain curve of epoxy resin matrix;
[0047] Figure 6Stress-strain curves of porous preform / epoxy resin composite floating body materials made by mixing microspheres with polyetheretherketone in different proportions;
[0048] Figure 7 The microstructure of the floating material of the present invention;
[0049] Figure 8 Longitudinal cracks appearing inside the sample along the direction of pressure under compressive stress;
[0050] Fig. 9 Flow chart of preparation of hollow glass microsphere / polyetheretherketone porous preform;
[0051] Fig.10 Particle size distribution of hollow glass microspheres. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0053] The stirring speed in the following examples and comparative examples is 400 rpm. The particle size of the hollow glass microspheres in the following examples and comparative examples is 20-120 μm.
[0054] Example 1
[0055] A method for preparing a high-performance hollow glass microsphere / epoxy resin floating material, the preparation steps are as follows:
[0056] Pour 900 mL of deionized water into a beaker, add 90 mL of hollow glass beads, stir at room temperature for 10 min, let stand for 2 h, and take the upper layer of hollow glass beads and filter and dry them.
[0057] 20 g of the floated hollow glass microspheres were placed in 200 mL of NaOH solution with a solution concentration of 0.75 mol / L, stirred at 50°C for 2 h, and allowed to stand for 30 min after stirring. The hollow glass microspheres were washed with deionized water until neutral, and then filtered and dried to obtain hydroxylated hollow glass microspheres.
[0058] 10g of hydroxylated hollow glass microspheres were placed in a mixed solution of 300mL of ethanol and deionized water in a volume ratio of 1:3. 1g of coupling agent KH-792 was added. Mechanical stirring was used for 2h at 80℃. After the reaction was completed, the surface was washed with deionized water, filtered and dried (110℃) to obtain hollow glass microspheres after surface treatment.
[0059] The surface treated hollow glass microspheres and polyetheretherketone were mixed in a mass ratio of 30:4 and poured into a quartz mold. The mold was placed on an oscillating device and oscillated for 15 minutes. The mold was then placed in a muffle furnace and heated to 370°C according to a preset sintering program (7°C per minute. Since the hollow glass microspheres are hollow structures with good thermal insulation, a too low heating rate will affect the molding speed. If the heating rate is too fast, the polyetheretherketone in the edge area will melt too quickly, while the central glass is still in a powder solid state, which has an adverse effect on the molding of the porous preform). The mixture was kept at 370°C for 15 minutes, the mold was taken out, and demolded after cooling to room temperature to obtain a hollow glass microsphere / polyetheretherketone porous preform.
[0060] The epoxy resin and the curing agent are mixed in a mass ratio of 3:1 and stirred evenly to obtain an epoxy resin mixed liquid.
[0061] The obtained porous preform is placed in a silicone rubber mold, and the epoxy resin mixture is poured into the silicone rubber mold to just cover the porous preform. The entire silicone rubber mold is placed in a small vacuum box, and after vacuuming and holding the pressure for 20 minutes, it is observed that the epoxy resin does not boil. The hollow glass microsphere preform filled with liquid epoxy resin is taken out together with the mold, heated to 80℃ for 5 hours to solidify, cooled naturally after solidification, and demolded.
[0062] The macroscopic and microscopic morphologies of the HGM porous preform obtained in this embodiment are as follows: Figure 2 As shown, polyetheretherketone plays a bonding role, bonding the hollow glass microspheres into a block with a certain strength structure. The purpose of forming the preform is mainly to fix the hollow glass microspheres, so that the hollow glass microspheres can be evenly dispersed in the epoxy resin matrix.
[0063] Example 2
[0064] A method for preparing a high-performance hollow glass microsphere / epoxy resin floating material, the preparation steps are as follows:
[0065] Pour 900 mL of deionized water into a beaker, add 90 mL of hollow glass beads, stir at room temperature for 10 min, let stand for 2 h, and take the upper layer of hollow glass beads and filter and dry them.
[0066] 20 g of the floated hollow glass microspheres were placed in 200 mL of NaOH solution with a solution concentration of 0.75 mol / L, stirred at 50°C for 2 h, and allowed to stand for 30 min after stirring. The hollow glass microspheres were washed with deionized water until neutral, and then filtered and dried to obtain hydroxylated hollow glass microspheres.
[0067] 10g of hydroxylated hollow glass microspheres were placed in a mixed solution of 300mL of ethanol and deionized water in a volume ratio of 1:3. 1g of coupling agent KH-792 was added. Mechanical stirring was used for 2h at 80℃. After the reaction was completed, the surface was washed with deionized water, filtered and dried (110℃) to obtain hollow glass microspheres after surface treatment.
[0068] The surface-treated hollow glass microspheres and polyetheretherketone are mixed in a mass ratio of 30:5 and poured into a quartz mold. The mold is placed on an oscillating device and shaken for 15 minutes. The mold is then placed in a muffle furnace and heated to 370°C according to a preset sintering program (temperature increase of 5°C per minute). The temperature is kept at 370°C for 15 minutes, the mold is taken out, and demolded after cooling to room temperature to obtain a hollow glass microsphere / polyetheretherketone porous preform.
[0069] The epoxy resin and the curing agent are mixed in a mass ratio of 3:1 and stirred evenly to obtain an epoxy resin mixed liquid.
[0070] The obtained porous preform is placed in a silicone rubber mold, and the epoxy resin mixture is poured into the silicone rubber mold to just cover the porous preform. The entire silicone rubber mold is placed in a small vacuum box, and after vacuuming and holding the pressure for 20 minutes, it is observed that the epoxy resin does not boil. The hollow glass microsphere preform filled with liquid epoxy resin is taken out together with the mold, heated to 80℃ for 4 hours to solidify, cooled naturally after solidification, and demolded.
[0071] Example 3
[0072] A method for preparing a high-performance hollow glass microsphere / epoxy resin floating material, the preparation steps are as follows:
[0073] Pour 900 mL of deionized water into a beaker, add 90 mL of hollow glass beads, stir at room temperature for 10 min, let stand for 2 h, and take the upper layer of hollow glass beads and filter and dry them.
[0074] 20 g of the floated hollow glass microspheres were placed in 200 mL of NaOH solution with a solution concentration of 0.75 mol / L, stirred at 50°C for 2 h, and allowed to stand for 30 min after stirring. The hollow glass microspheres were washed with deionized water until neutral, and then filtered and dried to obtain hydroxylated hollow glass microspheres.
[0075] 10g of hydroxylated hollow glass microspheres were placed in a mixed solution of 300mL of ethanol and deionized water in a volume ratio of 1:3. 1g of coupling agent KH-792 was added. Mechanical stirring was used for 2h at 80℃. After the reaction was completed, the surface was washed with deionized water, filtered and dried (110℃) to obtain hollow glass microspheres after surface treatment.
[0076] The surface-treated hollow glass microspheres and polyetheretherketone are mixed in a mass ratio of 30:6 and poured into a quartz mold. The mold is placed on an oscillating device and shaken for 15 minutes. The mold is then placed in a muffle furnace and heated to 380°C according to a preset sintering program (temperature increase of 10°C per minute). The mold is kept at 370°C for 15 minutes, the mold is taken out, and demolded after cooling to room temperature to obtain a hollow glass microsphere / polyetheretherketone porous preform.
[0077] The epoxy resin and the curing agent are mixed in a mass ratio of 3:1 and stirred evenly to obtain an epoxy resin mixed liquid.
[0078] The obtained porous preform is placed in a silicone rubber mold, and the epoxy resin mixture is poured into the silicone rubber mold to just cover the porous preform. The entire silicone rubber mold is placed in a small vacuum box, and after vacuuming and holding the pressure for 20 minutes, it is observed that the epoxy resin does not boil. The hollow glass microsphere preform filled with liquid epoxy resin is taken out together with the mold, heated to 80℃ for 6 hours to solidify, cooled naturally after solidification, and demolded.
[0079] Example 4
[0080] A method for preparing a high-performance hollow glass microsphere / epoxy resin floating material, the preparation steps are as follows:
[0081] Pour 900 mL of deionized water into a beaker, add 90 mL of hollow glass beads, stir at room temperature for 10 min, let stand for 2 h, and take the upper layer of hollow glass beads and filter and dry them.
[0082] 20 g of the floated hollow glass microspheres were placed in 200 mL of NaOH solution with a solution concentration of 0.75 mol / L, stirred at 50°C for 2 h, and allowed to stand for 30 min after stirring. The hollow glass microspheres were washed with deionized water until neutral, and then filtered and dried to obtain hydroxylated hollow glass microspheres.
[0083] 10g of hydroxylated hollow glass microspheres were placed in a mixed solution of 300mL of ethanol and deionized water in a volume ratio of 1:3. 1g of coupling agent KH-792 was added. Mechanical stirring was used for 2h at 80℃. After the reaction was completed, the surface was washed with deionized water, filtered and dried (110℃) to obtain hollow glass microspheres after surface treatment.
[0084] The surface-treated hollow glass microspheres and polyetheretherketone are mixed in a mass ratio of 30:7 and poured into a quartz mold. The mold is placed on an oscillating device and shaken for 15 minutes. The mold is then placed in a muffle furnace and heated to 370°C according to a preset sintering program (8°C per minute). The temperature is kept at 370°C for 15 minutes, the mold is taken out, and demolded after cooling to room temperature to obtain a hollow glass microsphere / polyetheretherketone porous preform.
[0085] The epoxy resin and the curing agent are mixed in a mass ratio of 3:1 and stirred evenly to obtain an epoxy resin mixed liquid.
[0086] The obtained porous preform is placed in a silicone rubber mold, and the epoxy resin mixture is poured into the silicone rubber mold to just cover the porous preform. The entire silicone rubber mold is placed in a small vacuum box, and after vacuuming and holding the pressure for 20 minutes, it is observed that the epoxy resin does not boil. The hollow glass microsphere preform filled with liquid epoxy resin is taken out together with the mold, heated to 80℃ for 5 hours to solidify, cooled naturally after solidification, and demolded.
[0087] Example 5
[0088] A method for preparing a high-performance hollow glass microsphere / epoxy resin floating material, the preparation steps are as follows:
[0089] Pour 900 mL of deionized water into a beaker, add 90 mL of hollow glass beads, stir at room temperature for 10 min, let stand for 2 h, and take the upper layer of hollow glass beads and filter and dry them.
[0090] 20 g of the floated hollow glass microspheres were placed in 200 mL of NaOH solution with a solution concentration of 0.75 mol / L, stirred at 50°C for 2 h, and allowed to stand for 30 min after stirring. The hollow glass microspheres were washed with deionized water until neutral, and then filtered and dried to obtain hydroxylated hollow glass microspheres.
[0091] 10g of hydroxylated hollow glass microspheres were placed in a mixed solution of 300mL of ethanol and deionized water in a volume ratio of 1:3. 1g of coupling agent KH-792 was added. Mechanical stirring was used for 2h at 80℃. After the reaction was completed, the surface was washed with deionized water, filtered and dried (110℃) to obtain hollow glass microspheres after surface treatment.
[0092] The surface-treated hollow glass microspheres and polyetheretherketone are mixed in a mass ratio of 30:8 and poured into a quartz mold. The mold is placed on an oscillating device and shaken for 15 minutes. The mold is then placed in a muffle furnace and heated to 370°C according to a preset sintering program (temperature increase of 7°C per minute). The temperature is kept at 370°C for 20 minutes, the mold is taken out, and demolded after cooling to room temperature to obtain a hollow glass microsphere / polyetheretherketone porous preform.
[0093] The epoxy resin and the curing agent are mixed in a mass ratio of 3:1 and stirred evenly to obtain an epoxy resin mixed liquid.
[0094] The obtained porous preform is placed in a silicone rubber mold, and the epoxy resin mixture is poured into the silicone rubber mold to just cover the porous preform. The entire silicone rubber mold is placed in a small vacuum box, and after vacuuming and holding the pressure for 20 minutes, it is observed that the epoxy resin does not boil. The hollow glass microsphere preform filled with liquid epoxy resin is taken out together with the mold, heated to 80℃ for 5 hours to solidify, cooled naturally after solidification, and demolded.
[0095] Comparative Example 1 (omitting the hydroxylation and coupling coating steps):
[0096] Pour 900 mL of deionized water into a beaker, add 90 mL of hollow glass beads, stir at room temperature for 10 min, let stand for 2 h, and take the upper layer of hollow glass beads and filter and dry them.
[0097] The hollow glass microspheres after flotation were mixed with polyetheretherketone in a mass ratio of 30:4 and poured into a quartz mold. The mold was placed on an oscillating device and oscillated for 15 minutes. The mold was then placed in a muffle furnace and heated to 370°C according to a preset sintering program (temperature increase of 7°C per minute). The mold was kept at 370°C for 15 minutes, and the mold was taken out and demolded after being cooled to room temperature to obtain a hollow glass microsphere / polyetheretherketone porous preform.
[0098] The epoxy resin and the curing agent are mixed in a mass ratio of 3:1 and stirred evenly to obtain an epoxy resin mixed liquid.
[0099] The obtained porous preform is placed in a silicone rubber mold, and the epoxy resin mixture is poured into the silicone rubber mold to just cover the porous preform. The entire silicone rubber mold is placed in a small vacuum box, and after vacuuming and holding the pressure for 20 minutes, it is observed that the epoxy resin does not boil. The hollow glass microsphere preform filled with liquid epoxy resin is taken out together with the mold, heated to 80℃ for 5 hours to solidify, cooled naturally after solidification, and demolded.
[0100] Comparative Example 2 (700°C high temperature sintering):
[0101] Pour 900 mL of deionized water into a beaker, add 90 mL of hollow glass beads, stir at room temperature for 10 min, let stand for 2 h, and take the upper layer of hollow glass beads and filter and dry them.
[0102] 20 g of the floated hollow glass microspheres were placed in 200 mL of NaOH solution with a solution concentration of 0.75 mol / L, stirred at 50°C for 2 h, and allowed to stand for 30 min after stirring. The hollow glass microspheres were washed with deionized water until neutral, and then filtered and dried to obtain hydroxylated hollow glass microspheres.
[0103] 10g of hydroxylated hollow glass microspheres were placed in a mixed solution of 300mL of ethanol and deionized water in a volume ratio of 1:3. 1g of coupling agent KH-792 was added. Mechanical stirring was used for 2h at 80℃. After the reaction was completed, the surface was washed with deionized water, filtered and dried (110℃) to obtain hollow glass microspheres after surface treatment.
[0104] The surface treated hollow glass microspheres were placed in a quartz mold, and then the mold was placed in a muffle furnace for high temperature sintering at 700°C. After keeping the temperature for 15 minutes, the mold was taken out and demolded after cooling to room temperature to obtain a hollow glass microsphere block.
[0105] The epoxy resin and the curing agent are mixed in a mass ratio of 3:1 and stirred evenly to obtain an epoxy resin mixed liquid.
[0106] The obtained hollow glass microsphere block is placed in a silicone rubber mold, and the epoxy resin mixture is poured into the silicone rubber mold to just submerge the hollow glass microsphere block. The entire silicone rubber mold is placed in a small vacuum box, and after vacuuming and maintaining pressure for 20 minutes, it is observed that the epoxy resin does not boil. The hollow glass microsphere preform filled with liquid epoxy resin is taken out together with the mold, heated to 80℃ for 5 hours to solidify, cooled naturally after solidification, and demolded to obtain a solid floating material.
[0107] Comparative Example 3 (replacing polyetheretherketone with polypropylene):
[0108] Pour 900 mL of deionized water into a beaker, add 90 mL of hollow glass beads, stir at room temperature for 10 min, let stand for 2 h, and take the upper layer of hollow glass beads and filter and dry them.
[0109] 20 g of the floated hollow glass microspheres were placed in 200 mL of NaOH solution with a solution concentration of 0.75 mol / L, stirred at 50°C for 2 h, and allowed to stand for 30 min after stirring. The hollow glass microspheres were washed with deionized water until neutral, and then filtered and dried to obtain hydroxylated hollow glass microspheres.
[0110] 10g of hydroxylated hollow glass microspheres were placed in a mixed solution of 300mL of ethanol and deionized water in a volume ratio of 1:3. 1g of coupling agent KH-792 was added. Mechanical stirring was used for 2h at 80℃. After the reaction was completed, the surface was washed with deionized water, filtered and dried (110℃) to obtain hollow glass microspheres after surface treatment.
[0111] The hollow glass microspheres treated with a coupling agent and polypropylene were mixed in a mass ratio of 30:4 and poured into a quartz mold. The mold was placed on an oscillating device and oscillated for 15 minutes. The mold was then placed in a muffle furnace and heated to 170°C according to a preset sintering program (temperature increase of 7°C per minute). The mold was kept at 170°C for 15 minutes, and the mold was taken out and demolded after being cooled to room temperature to obtain a hollow glass microsphere / polypropylene porous preform.
[0112] The epoxy resin and the curing agent are mixed in a mass ratio of 3:1 and stirred evenly to obtain an epoxy resin mixed liquid.
[0113] The obtained porous preform is placed in a silicone rubber mold, and the epoxy resin mixture is poured into the silicone rubber mold to just cover the porous preform. The entire silicone rubber mold is placed in a small vacuum box, and after vacuuming and holding the pressure for 20 minutes, it is observed that the epoxy resin does not boil. The hollow glass microsphere preform filled with liquid epoxy resin is taken out together with the mold, heated to 80℃ for 5 hours to solidify, cooled naturally after solidification, and demolded.
[0114] Comparative Example 4 (omitting the coupling coating step):
[0115] Pour 900 mL of deionized water into a beaker, add 90 mL of hollow glass beads, stir at room temperature for 10 min, let stand for 2 h, and take the upper layer of hollow glass beads and filter and dry them.
[0116] 20 g of the floated hollow glass microspheres were placed in 200 mL of NaOH solution with a solution concentration of 0.75 mol / L, stirred at 50°C for 2 h, and allowed to stand for 30 min after stirring. The hollow glass microspheres were washed with deionized water until neutral, and then filtered and dried to obtain hydroxylated hollow glass microspheres.
[0117] The hydroxylated hollow glass microspheres and polyetheretherketone were mixed in a mass ratio of 30:4 and poured into a quartz mold. The mold was placed on an oscillating device and oscillated for 15 minutes. The mold was then placed in a muffle furnace and heated to 370°C according to a preset sintering program (temperature increase of 7°C per minute). The mold was kept at 370°C for 15 minutes, the mold was taken out, and demolded after being cooled to room temperature to obtain a hollow glass microsphere / polyetheretherketone porous preform.
[0118] The epoxy resin and the curing agent are mixed in a mass ratio of 3:1 and stirred evenly to obtain an epoxy resin mixed liquid.
[0119] The obtained porous preform is placed in a silicone rubber mold, and the epoxy resin mixture is poured into the silicone rubber mold to just cover the porous preform. The entire silicone rubber mold is placed in a small vacuum box, and after vacuuming and holding the pressure for 20 minutes, it is observed that the epoxy resin does not boil. The hollow glass microsphere preform filled with liquid epoxy resin is taken out together with the mold, heated to 80℃ for 5 hours to solidify, cooled naturally after solidification, and demolded.
[0120] Comparative Example 5 (omitting the hydroxylation step):
[0121] Pour 900 mL of deionized water into a beaker, add 90 mL of hollow glass beads, stir at room temperature for 10 min, let stand for 2 h, and take the upper layer of hollow glass beads and filter and dry them.
[0122] 10g of the hollow glass microspheres after flotation were placed in a mixed solution of 300mL of ethanol and deionized water in a volume ratio of 1:3. 1g of coupling agent KH-792 was added. Mechanical stirring was used for 2h at 80℃. After the reaction was completed, it was washed with deionized water, filtered and dried (110℃) to obtain hollow glass microspheres after coupling coating treatment.
[0123] The hollow glass microspheres after coupling coating treatment and polyetheretherketone are mixed in a mass ratio of 30:4 and poured into a quartz mold. The mold is placed on an oscillating device and shaken for 15 minutes. The mold is then placed in a muffle furnace and heated to 370°C according to a preset sintering program (temperature increase of 7°C per minute). The temperature is kept at 370°C for 15 minutes, the mold is taken out, and demolded after cooling to room temperature to obtain a hollow glass microsphere / polyetheretherketone porous preform.
[0124] The epoxy resin and the curing agent are mixed in a mass ratio of 3:1 and stirred evenly to obtain an epoxy resin mixed liquid.
[0125] The obtained porous preform is placed in a silicone rubber mold, and the epoxy resin mixture is poured into the silicone rubber mold to just cover the porous preform. The entire silicone rubber mold is placed in a small vacuum box, and after vacuuming and holding the pressure for 20 minutes, it is observed that the epoxy resin does not boil. The hollow glass microsphere preform filled with liquid epoxy resin is taken out together with the mold, heated to 80℃ for 5 hours to solidify, cooled naturally after solidification, and demolded.
[0126] Comparative Example 6 (reducing the mass ratio of hollow glass microspheres to polyetheretherketone):
[0127] Pour 900 mL of deionized water into a beaker, add 90 mL of hollow glass beads, stir at room temperature for 10 min, let stand for 2 h, and take the upper layer of hollow glass beads and filter and dry them.
[0128] 20 g of the floated hollow glass microspheres were placed in 200 mL of NaOH solution with a solution concentration of 0.75 mol / L, stirred at 50°C for 2 h, and allowed to stand for 30 min after stirring. The hollow glass microspheres were washed with deionized water until neutral, and then filtered and dried to obtain hydroxylated hollow glass microspheres.
[0129] 10g of hydroxylated hollow glass microspheres were placed in a mixed solution of 300mL of ethanol and deionized water in a volume ratio of 1:3. 1g of coupling agent KH-792 was added. Mechanical stirring was used for 2h at 80℃. After the reaction was completed, the surface was washed with deionized water, filtered and dried (110℃) to obtain hollow glass microspheres after surface treatment.
[0130] The surface-treated hollow glass microspheres and polyetheretherketone were mixed in a mass ratio of 30:3 and poured into a quartz mold. The mold was placed on an oscillating device and oscillated for 15 minutes. The mold was then placed in a muffle furnace and heated to 370°C according to a preset sintering program (temperature increase of 7°C per minute). The mold was kept at 370°C for 15 minutes, and the mold was taken out and demolded after being cooled to room temperature to obtain a hollow glass microsphere / polyetheretherketone porous preform.
[0131] The epoxy resin and the curing agent are mixed in a mass ratio of 3:1 and stirred evenly to obtain an epoxy resin mixed liquid.
[0132] The obtained porous preform is placed in a silicone rubber mold, and the epoxy resin mixture is poured into the silicone rubber mold to just cover the porous preform. The entire silicone rubber mold is placed in a small vacuum box, and after vacuuming and holding the pressure for 20 minutes, it is observed that the epoxy resin does not boil. The hollow glass microsphere preform filled with liquid epoxy resin is taken out together with the mold, heated to 80℃ for 5 hours to solidify, cooled naturally after solidification, and demolded.
[0133] Comparative Example 7 (increasing the mass ratio of hollow glass microspheres to polyetheretherketone):
[0134] Pour 900 mL of deionized water into a beaker, add 90 mL of hollow glass beads, stir at room temperature for 10 min, let stand for 2 h, and take the upper layer of hollow glass beads and filter and dry them.
[0135] 20 g of the floated hollow glass microspheres were placed in 200 mL of NaOH solution with a solution concentration of 0.75 mol / L, stirred at 50°C for 2 h, and allowed to stand for 30 min after stirring. The hollow glass microspheres were washed with deionized water until neutral, and then filtered and dried to obtain hydroxylated hollow glass microspheres.
[0136] 10g of hydroxylated hollow glass microspheres were placed in a mixed solution of 300mL of ethanol and deionized water in a volume ratio of 1:3. 1g of coupling agent KH-792 was added. Mechanical stirring was used for 2h at 80℃. After the reaction was completed, the surface was washed with deionized water, filtered and dried (110℃) to obtain hollow glass microspheres after surface treatment.
[0137] The surface-treated hollow glass microspheres and polyetheretherketone were mixed in a mass ratio of 30:15 and poured into a quartz mold. The mold was placed on an oscillating device and oscillated for 15 minutes. The mold was then placed in a muffle furnace and heated to 370°C according to a preset sintering program (temperature increase of 7°C per minute). The mold was kept at 370°C for 15 minutes, the mold was taken out, and demolded after being cooled to room temperature to obtain a hollow glass microsphere / polyetheretherketone porous preform.
[0138] The epoxy resin and the curing agent are mixed in a mass ratio of 3:1 and stirred evenly to obtain an epoxy resin mixed liquid.
[0139] The obtained porous preform is placed in a silicone rubber mold, and the epoxy resin mixture is poured into the silicone rubber mold to just cover the porous preform. The entire silicone rubber mold is placed in a small vacuum box, and after vacuuming and holding the pressure for 20 minutes, it is observed that the epoxy resin does not boil. The hollow glass microsphere preform filled with liquid epoxy resin is taken out together with the mold, heated to 80℃ for 5 hours to solidify, cooled naturally after solidification, and demolded.
[0140] Comparative Example 8 (omitting the preform preparation step):
[0141] Pour 900 mL of deionized water into a beaker, add 90 mL of hollow glass beads, stir at room temperature for 10 min, let stand for 2 h, and take the upper layer of hollow glass beads and filter and dry them.
[0142] 20 g of the floated hollow glass microspheres were placed in 200 mL of NaOH solution with a solution concentration of 0.75 mol / L, stirred at 50°C for 2 h, and allowed to stand for 30 min after stirring. The hollow glass microspheres were washed with deionized water until neutral, and then filtered and dried to obtain hydroxylated hollow glass microspheres.
[0143] 10g of hydroxylated hollow glass microspheres were placed in a mixed solution of 300mL of ethanol and deionized water in a volume ratio of 1:3. 1g of coupling agent KH-792 was added. Mechanical stirring was used for 2h at 80℃. After the reaction was completed, the surface was washed with deionized water, filtered and dried (110℃) to obtain hollow glass microspheres after surface treatment.
[0144] The epoxy resin and the curing agent are mixed in a mass ratio of 3:1 and stirred evenly to obtain an epoxy resin mixed liquid.
[0145] The epoxy resin mixture and the surface treated hollow glass microspheres are stirred evenly, and then the slurry is poured into a mold and heated to 80°C for 5 hours to solidify. After solidification, it is naturally cooled and demoulded.
[0146] Detection:
[0147] The compressive strength, density and water absorption rate of the hollow glass microsphere / epoxy resin floating body materials prepared in the above Examples 1-5 and Comparative Examples 1-8 were tested, and the results are shown in Table 1 below:
[0148] Table 1 Performance parameters of hollow glass microsphere / epoxy resin float material
[0149]
[0150]
[0151] Among them, the determination of compressive strength and stress-strain curve: the compression test of the floating material is tested according to the GB / T1041-1992 standard to obtain the compressive strength and stress-strain curve. The test sample size is 10mm×10mm×20mm. The compression test is tested on an electronic universal testing machine (Instron5569). The pressure head loading rate is 0.5mm / min. The compression stress-strain curve of the compression sample is recorded, and the compression elastic modulus is calculated according to the compression stress-strain curve of the sample. The formula for calculating the compressive strength of the composite material is:
[0152] σc=N / S (1)
[0153] Where σc——compressive strength, MPa;
[0154] N——load borne by the specimen, N; S——cross-sectional area of the specimen, mm 2 .
[0155] Open porosity test method for porous preforms:
[0156] The density and open porosity are tested according to GB / T 1966-1996 "Test Method for Apparent Porosity and Bulk Density of Porous Ceramics". First, clean the surface of the sample, place it in a 110° air drying oven and dry it for 2 hours, and use a high-precision analytical balance (accuracy 0.1 mg) to weigh the mass as m1. After the sample is placed in a container filled with deionized water and boiled for 2 hours, the heating is stopped, and it is cooled to room temperature. After wiping off excess water on the surface of the sample, the mass weighed in the air is m2; the mass weighed in water is m3. The calculation formula for the density and porosity of HGM porous ceramics is as follows:
[0157]
[0158] At least 5 samples were measured in each group, the average value was taken and the error limit was calculated.
[0159] Test method for water absorption of composite materials:
[0160] The water absorption rate of materials is tested in accordance with GB / T1034-2008 "Determination of water absorption of materials". The sample size is Φ50×3mm. Three samples are tested in each group of experiments to get the average value. First, the sample is placed in a 50℃ oven and dried for 24 hours, then cooled to room temperature in a dryer, and the weighed mass is recorded as m1. Then the sample is immersed in room temperature, 50℃ deionized water or simulated seawater solution, and the sample is taken out at regular intervals. After the sample is removed, the surface of the sample is wiped with filter paper, and its mass is quickly weighed, recorded as m2. The calculation formula for the water absorption rate w of the composite material is:
[0161]
[0162] The open porosity of the porous preforms obtained in Examples 1-5 is about 35%, and the microbead filling rate = (100% - open porosity) * ((HGM filling mass / HGM true density) / (HGM filling mass / HGM true density) + (filling mass of polyetheretherketone / density of polyetheretherketone). The true density of HGM used in this patent is 0.6 g / cm 3 , the density of polyetheretherketone is 1.3g / cm 3 .
[0163] In Comparative Example 1, hollow glass microspheres without modified hydroxyl groups and coupling agents were used to prepare a preform with polyetheretherketone, and then a composite material was prepared with epoxy resin, and its strength decreased significantly. The hollow glass microspheres without modified hydroxyl groups and coupling agents had poor interfacial bonding with epoxy resin during curing, which affected the strength and elastic modulus. Hydroxyl groups and silane coupling agents enhanced the bonding performance of hollow glass microspheres with polyetheretherketone. When forming a preform, the hollow glass microspheres without modified hydroxyl groups and coupling agents were not tightly bonded to polyetheretherketone (observed with the naked eye), that is, some hollow glass microspheres were not successfully bonded in the preform, and were easily separated from the preform, resulting in a decrease in the microsphere filling rate.
[0164] In Comparative Example 2, the microbeads were sintered into a preform at a high temperature of 700° C., and the microbeads were softened significantly, and their shapes were changed, and the strength and elastic modulus of the final composite material also decreased.
[0165] In Comparative Example 3, polypropylene resin was used, and the strength and elastic modulus of the final composite material decreased.
[0166] In Comparative Example 4, no coupling agent modification was performed, which directly affected the interfacial bonding strength between the hollow glass microspheres and polyetheretherketone and epoxy resin, and ultimately the strength and elastic modulus of the floating material decreased.
[0167] In comparative example 5, no hydroxyl modification is performed, which is not conducive to coupling agent modification. The coupling agent adhesion state is not as good as that of examples 1-5, which affects the interfacial bonding strength between the hollow glass microspheres and polyetheretherketone and epoxy resin, and finally the strength and elastic modulus of the floating material decrease.
[0168] In Comparative Example 6, the mass ratio of the surface-treated hollow glass microspheres to polyetheretherketone is 30:3, and the amount of polyetheretherketone added is too low to achieve the molding of the preform, so that the final composite material cannot be molded. Figure 3 As shown in b, powder falling off can be clearly seen.
[0169] In Comparative Example 7, the mass ratio of hollow glass microspheres to polyetheretherketone is 30:15. Since polyetheretherketone is used in excessive amount, it replaces the position of hollow glass microspheres and has a greater impact on the filling amount of hollow glass microspheres.
[0170] In Comparative Example 8, because the mixing and pouring method is used, irregular bubbles will be generated inside the composite material, and the strength of the composite material will be significantly reduced. After the compression test, the composite material obtained has macro cracks, such as Figure 4 shown.
[0171] Figure 1 A flow chart for preparing the floating material of the present invention; Figure 2 The macroscopic and microscopic morphologies of the HGM porous preform (Example 1), a, macroscopic morphology, b, microscopic morphology, the HGM porous preforms prepared in Examples 2-5 and Figure 2 Closely, the hollow glass microspheres and PEEK are closely combined, and the hollow glass microspheres are evenly distributed in the porous preform; Figure 3 To prepare successful or failed preforms: (a) Example 1, (b) Comparative Example 6; Figure 4 Compression diagram of the floating material. After the compression test, the floating material showed macro cracks (Comparative Example 8).
[0172] Figure 5 The stress-strain curve of the epoxy resin used to prepare the floating material (only epoxy resin and curing agent are mixed in a mass ratio of 3:1 to prepare epoxy resin blocks, without adding hollow glass microspheres or preforms, and the compressive strength is measured to obtain the stress-strain curve). The compressive strength calculation formula is shown in formula (1).
[0173] Figure 6 From the stress-strain curves of the porous preform / epoxy resin composite materials prepared by mixing microspheres and polyetheretherketone in different proportions in Examples 1-5, it can be seen that the compressive resistance of the porous preform / epoxy resin composite floating body materials in Examples 1-5 is better.
[0174] Figure 7 The microstructure of the floating material, Figure 7(a) corresponds to Example 1 (no bubbles in the microstructure), Figure 7 (b) in the figure corresponds to Example 8 (air bubbles in the microstructure). The composite materials prepared in Examples 2-5 are similar to those in Example 1, and there are no air bubbles in the microstructure. Only the composite materials prepared by the stirring casting method will produce air bubbles. Figure 7 As shown in (b); Comparative Example 1 is Figure 7 As shown in (c) of Figure 7 Compared with (a), about half of the microbeads were not firmly bonded and fell off; microbeads also fell off in Comparative Examples 4 and 5.
[0175] Figure 8 The longitudinal cracks that appeared inside the sample under the ultimate compressive stress of 85MPa along the pressure direction correspond to Example 1. The hollow glass microspheres are tightly bonded to the epoxy resin matrix and are longitudinally fractured from the middle of the hollow glass microspheres. This shows that the interface bonding is strong and the load transfer is effective. However, the brittleness and strength limitation of the hollow glass microspheres cause the microspheres themselves to break when subjected to a large external force. This fracture mode reflects the good bonding and certain toughness of the composite material. The floating materials prepared in Examples 2-5 are similar to Figure 8 Close-up, longitudinal cracks appearing inside the sample along the direction of pressure under compressive stress.
[0176] Fig. 9 Flow chart of preparation of hollow glass microsphere / polyetheretherketone porous preform;
[0177] Fig.10 The particle size distribution diagram of hollow glass microspheres shows the particle size distribution of the hollow glass microsphere raw materials used.
[0178] It should be understood that the above embodiments do not limit the present invention in any form, and any technical solutions obtained by equivalent replacement or equivalent transformation shall fall within the protection scope of the present invention.
Claims
1. A method for preparing high-performance hollow glass microsphere / epoxy resin floating material, characterized in that: The preparation process is as follows: (1) hydroxylating and coupling agent coating the hollow glass microspheres to obtain surface-treated hollow glass microspheres; (2) mixing the surface-treated hollow glass microspheres and polyetheretherketone in a uniform proportion, placing them into a mold and sintering them in a muffle furnace, wherein the sintering process is as follows: heating to 370°C-380°C at a heating rate of 5-10°C / min and keeping the temperature for 15-20min, cooling, and demolding to obtain a porous preform; wherein the mass ratio of the surface-treated hollow glass microspheres to the polyetheretherketone is 30:4-8; (3) mixing the epoxy resin and the curing agent in proportion and stirring evenly to obtain an epoxy resin mixed solution; (4) placing the porous preform obtained in step (2) in a cavity mold, injecting the epoxy resin mixture obtained in step (3), evacuating and maintaining pressure for a period of time, heating and curing, cooling, and demolding.
2. The method for preparing a high-performance hollow glass microsphere / epoxy resin floating material according to claim 1, characterized in that: Step (2) is specifically as follows: mixing the surface-treated hollow glass microspheres with the polyetheretherketone powder and pouring the mixture into a mold, placing the mold containing the surface-treated hollow glass microspheres and the polyetheretherketone powder on an oscillating device, and oscillating the mold for a period of time so that the polyetheretherketone powder is evenly mixed on the surface of the hollow glass microspheres and is sufficiently densely stacked; then, placing the mold containing the densely stacked polyetheretherketone powder and the hollow glass microspheres in a muffle furnace, gradually heating to 370°C-380°C, keeping the temperature for 15-20 minutes, cooling to room temperature, and demolding to obtain a hollow glass microsphere / polyetheretherketone porous preform.
3. The method for preparing high-performance hollow glass microsphere / epoxy resin floating material according to claim 1, characterized in that: In step (1), before the hollow glass microspheres are subjected to hydroxylation and coupling agent coating treatment, the hollow glass microspheres are subjected to flotation treatment; in the flotation treatment, the operation steps are: mixing the hollow glass microspheres with pure water in proportion, stirring at a certain speed, taking the upper layer of microspheres after standing for a certain time, and drying to obtain the hollow glass microspheres after flotation; in the flotation treatment, when the hollow glass microspheres are soaked in pure water, the volume ratio of the hollow glass microspheres to water is 1:8-12; in the flotation treatment, the stirring time is 5-15 minutes, and the stirring needs to be allowed to stand for 1-3 hours.
4. The method for preparing a high-performance hollow glass microsphere / epoxy resin floating material according to claim 1, characterized in that: In step (1), the hollow glass microspheres are hydroxylated with a 0.6-1.0 mol / L NaOH solution, and the solution is stirred during the hydroxylation. During the hydroxylation, the temperature is 40-60°C, the treatment time is 1.5-2.5h, and the stirring rate is 300-500rpm. The mass volume ratio of the hollow glass microspheres to the NaOH solution is 1g: (8-12)mL.
5. The method for preparing high-performance hollow glass microsphere / epoxy resin floating material according to claim 1, characterized in that: During the coupling agent coating process, the hollow glass microspheres after hydroxylation treatment are placed in an ethanol solution, which is a mixture of anhydrous ethanol and deionized water in a volume ratio of 1:3, and then a high-temperature resistant silane coupling agent KH-792 is added, and stirred at 70-90 ° C for 1.5-2.5 h; the hollow glass microspheres after surface treatment are taken, washed, and dried at 110-120 ° C to complete the curing of the coupling agent and the formation of chemical bonds.
6. The method for preparing a high-performance hollow glass microsphere / epoxy resin floating material according to claim 4, characterized in that: In the coupling agent coating process, the coupling agent used is a high temperature resistant silane coupling agent KH-792. The presence of diamino groups increases the reaction opportunities and improves the interface bonding strength. The mass ratio of the coupling agent to the hollow glass microspheres after hydroxylation is 1:7-13; the mass volume ratio of the hollow glass microspheres after hydroxylation to the ethanol solution is 1g:(20-40)mL.
7. The method for preparing high-performance hollow glass microsphere / epoxy resin floating material according to claim 2, characterized in that: The mold for containing the surface-treated hollow glass microspheres and polyetheretherketone in step (2) is a quartz mold.
8. The method for preparing a high-performance hollow glass microsphere / epoxy resin floating material according to claim 1, characterized in that: In step (3), the mass ratio of epoxy resin to curing agent is 2.5-3.5:1; the epoxy resin is liquid epoxy resin.
9. The method for preparing a high-performance hollow glass microsphere / epoxy resin floating material according to claim 1, characterized in that: In step (3), the epoxy resin is E-51 epoxy resin, and the curing agent is amine curing agent HS-273M.
10. The method for preparing high-performance hollow glass microsphere / epoxy resin floating material according to claim 1, characterized in that: Step (4) is specifically as follows: placing the porous preform obtained in step (2) in a mold, pouring the epoxy resin mixture obtained in step (3) into the mold, and making the epoxy resin mixture submerge the porous preform; placing the entire mold in a vacuum box, evacuating and maintaining pressure until the epoxy resin does not boil, and a hollow glass microsphere preform filled with liquid epoxy resin is formed in the mold; taking out the hollow glass microsphere preform filled with liquid epoxy resin together with the mold, heating to 70-90°C and keeping warm for 4-6 hours, cooling after solidification, and demolding to obtain the final floating material.
Citation Information
Patent Citations
Solid buoyancy material with high impact strength and preparation method thereof
CN103865235A
A high-strength solid buoyancy material and its preparation method
CN110698815B
A method for preparing a solid buoyancy material composed of hybrid hollow glass microspheres
CN112694717B
High-strength solid buoyancy material and preparation method thereof
CN114381088A
Lightweight pressure-resistant material as well as preparation method and application thereof
CN118165393A
Cited By
Optimization and preparation method of epoxy resin floating body material based on relaxation-vonoroi graph optimization algorithm
CN120180772A
Optimization and preparation method of epoxy resin floating body material based on relaxation-vonoroi diagram optimization algorithm
CN120180772B
High-strength low-density epoxy SMC composite material and preparation method thereof
CN121045742A
High-strength low-density epoxy SMC composite material and preparation method thereof
CN121045742B
Deep rock in-situ heat preservation coring microbead composite material and preparation method thereof
CN121427250A